Understanding a reader's attraction to a literary short text - Banegas, Darío Luis (Colombian Applied Linguistics Journal, 2014)
The aim of this article is to understand why a reader may feel attracted to a short piece of fictional discourse. I analyse a short extract taken from Khaled Hosseini’s novel A Thousand Splendid Suns through the integration of different perspectives in discourse analysis. First, I analyse the text in terms of contexts of culture and situation including field, tenor, mode, participants’ social world, setting, channel, and key. In the second section, I attempt to examine the text line by line following my interdisciplinary framework of reference. Secondly, I offer a line-by-line analysis through Grice’s maxims, topicality, deixis, coding time, types of utterances and verbal processes, and metaphors. Through my analysis, I discovered that my attraction as a reader was based on the combination and integration of different textual devices and my personal interpretation of the pragmatics behind the text.